Sosialisme dalam Kajian Ilmu Filsafat - Sunaryo, Suparman (Yayasan Sembilan Pemuda Indonesia, 2023)
This article explores the role and conception of socialism in philosophical studies, exploring the roots of thought, theories, values, and concepts underlying socialist ideology. This study discusses the evolution of socialism from a historical perspective and its philosophical consequences on societal, political, and economic structures. The writing method is done by article review. Furthermore, it was found that the solution offered by Islamic Socialism was that Islam had exemplified its values, including love of justice, opposition to oppression, and belief in the macrocosmic transcendence of Allah and microcosmic transcendence of fellow human beings. Modern socialism emerged as a reaction to the plight of the people under greedy liberal capitalism. There is moderate socialism that champions its ideals in a “soft” way, and there is “radical” socialism that seeks to bring about the ideal conditions of society through revolution. Understanding related to socialism in philosophical studies plays an important role in presenting knowledge, especially in Indonesia.